New Insights Into the Relationship Between Drought and Mental Health Emerging From the Australian Rural Mental Health Study - Luong, Tuyen T.; Handley, Tonelle; Austin, Emma K.; Kiem, Anthony S.; Rich, Jane L.; Kelly, Brian (Frontiers in Psychiatry, 2021)
While it is recognized that drought affects mental health, few population-based longitudinal studies quantify this relationship. In this study, we investigate the effects of drought on mental health in a rural population, and how these effects change with continued exposure to drought conditions. Using a panel dataset consisting of 6519 observations from the Australian Rural Mental Health Study, we found a nonlinear (inverted U-shape) relationship between drought exposure and mental health. Specifically, people experienced an increase of psychological distress for the first 2.5 - 3 years of drought, after which time this distress dissipates. These effects were maintained after controlling for demographic, social, and environmental factors. We also found that while psychological distress decreases in the later stages of drought, this does not necessarily mean people have good mental health because, for example, factors such as life satisfaction decreased as drought persisted. This is important as it highlights the need for sustained support to mitigate the long-term effects of drought on mental health that persist after the drought has apparently finished.